Repetitive member factor study for cold-formed steel framing systems - Clayton, Scott (Kansas State University, 2010)
Cold-formed steel has become a preferred building material for structural farming in many different types of structures, commonly for repetitive members such as floor joists, roof rafters, roof trusses and wall studs. For wood framed structures with repetitive members, a repetitive member factor increases the allowable bending stress from 1.00 to 1.50 times the reference design value, depending on both the type of material and the type of load. Currently, however, the bending strength of cold-formed steel repetitive members is not permitted to be increased, even though the method of framing is quite similar to that of wood except for the material properties. Typical light-frame wood construction consists of floor, roof, and wall systems, each with repetitive members connected by sheathing. A repetitive system is one of at least three members that are spaced not farther apart than 24-inches. These members must also be joined by a load distributing element adequate to support the design load. The behavior of the individual members, then, is affected by inclusion into this system. Additionally, the connected sheathing increases the bending capacity of bending members due to both composite action and load sharing. Composite action is a result of T-beam-like action between the repetitive member and connected sheathing, but is limited by nail slippage in the connection. Secondly, due to differential deflection between the members, sheathing is also able to distribute loads from weaker, more flexible members to the more rigid and stronger members. This effect is known as load-sharing. The same general principles of repetitive use should apply to cold-formed steel due to its similarity to wood construction. Accordingly, this paper conducts a preliminary study of the effects of both composite action and load-sharing in cold-formed steel assemblies and subsequently recommends using a repetitive member factor for cold-formed steel members.
Keywords: Repetitive member factor; Cold-formed steel; Engineering, Civil (0543); Engineering, General (0537)